2011
DOI: 10.1136/thoraxjnl-2011-201231
|View full text |Cite
|
Sign up to set email alerts
|

Thorax in focus: chronic obstructive pulmonary disease

Abstract: Keeping up to date with scientific developments in any field of medicine is challenging, and chronic obstructive pulmonary disease (COPD) is no exception. Thorax has played an important part in the communication of key developments to its readership. In this article we review original research published in the journal over the last 2-3 years. We consider scientific and clinical developments in the epidemiology, mechanisms and treatment of COPD, placing these articles in the context of other relevant literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…COPD is accompanied by inflammation and tissue remodelling,55 and has been known to be strongly associated with lung cancer. A recent study found a robust genomic link between COPD, lung cancer and Hedgehog signalling, which is also implicated in tobacco-smoke-induced EMT 56.…”
Section: Emt In Copdmentioning
confidence: 99%
“…COPD is accompanied by inflammation and tissue remodelling,55 and has been known to be strongly associated with lung cancer. A recent study found a robust genomic link between COPD, lung cancer and Hedgehog signalling, which is also implicated in tobacco-smoke-induced EMT 56.…”
Section: Emt In Copdmentioning
confidence: 99%
“…observed a fivefold increase in risk of cardiovascular disease, a threefold increase in risk of stroke and a twofold increase in risk of diabetes in patients with physician‐diagnosed COPD . Suggested mechanisms, over and above smoking, that may be implicated in these interactions include increased aortic stiffness and associated left ventricular dysfunction, as well as increased platelet activation . Of note is the fact that having COPD increases the risk of lung cancer by up to 4.5‐fold among long‐term smokers .…”
Section: Systemic Effects and Comorbiditiesmentioning
confidence: 99%
“…14 Suggested mechanisms, over and above smoking, that may be implicated in these interactions include increased aortic stiffness and associated left ventricular dysfunction, as well as increased platelet activation. 15 Of note is the fact that having COPD increases the risk of lung cancer by up to 4.5-fold among long-term smokers. 16 Considering lung-and non-lung-related manifestations of COPD as a 'syndrome' akin to the way in which we think of the metabolic syndrome, for example, may encourage investigation and appropriate management of some of the more common comorbidities described in association with COPD, including those mentioned as well as osteoporosis, hyperlipidaemia, hypertension, skeletal muscle abnormalities, anxiety and depression.…”
Section: Systemic Effects and Comorbiditiesmentioning
confidence: 99%
“…In contrast to previous recommendations, the new GOLD guidelines place less emphasis on spirometry testing for the evaluation of disease severity than on the evaluation of symptoms. The absolute level of FEV1 is no longer considered Treatment to be the only tool for severity classification in COPD, based on its lack of reliability as a marker for the severity of dyspnea, exercise limitation and health status impairment 2,6 .…”
Section: Overview Of the Gold-2011 Guidelines For Copd Assessmentmentioning
confidence: 99%
“…It is estimated that COPD will be the third leading cause of death worldwide and the fifth leading contributor to global disease burden by 2020 1 . The main pathological feature of COPD is persistent restricted respiratory airflow caused by chronic airway inflammation, which leads to decreased physical activity, fatigue and dyspnea 2 .…”
Section: Introductionmentioning
confidence: 99%